Heuristic Evaluation of Online COPD Respiratory Therapy and Education Video Resource Center - Stellefson, Michael (Mary Ann Liebert, Inc., 2014)
Purpose: Because of limited accessibility to pulmonary rehabilitation programs, patients with chronic obstructive pulmonary disease (COPD) are infrequently provided with patient education resources. To help educate patients with COPD on how to live a better life with diminished breathing capacity, we developed a novel social media resource center containing COPD respiratory therapy and education videos called “COPDFlix.” Methodology: A heuristic evaluation of COPDFlix was conducted as part of a larger study to determine whether the prototype was successful in adhering to formal Web site usability guidelines for older adults. A purposive sample of three experts, with expertise in Web design and health communications technology, was recruited (a) to identify usability violations and (b) to propose solutions to improve the functionality of the COPDFlix prototype. Each expert evaluated 18 heuristics in four categories of task-based criteria (i.e., interaction and navigation, information architecture, presentation design, and information design). Seventy-six subcriteria across these four categories were assessed. Quantitative ratings and qualitative comments from each expert were compiled into a single master list, noting the violated heuristic and type/location of problem(s). Results: Sixty-one usability violations were identified across the 18 heuristics. Evaluators rated the majority of heuristic subcriteria as either a “minor hindrance” (n=32) or “no problem” (n=132). Moreover, only 2 of the 18 heuristic categories were noted as “major” violations, with mean severity scores of ≥3. Conclusions: Mixed-methods data analysis helped the multidisciplinary research team to categorize and prioritize usability problems and solutions, leading to 26 discrete design modifications within the COPDFlix prototype.